2006
DOI: 10.1039/b509351a
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of vibrational circular dichroismspectra ofd-lactic acid–water complexes

Abstract: This paper presents a discussion of the interaction energies, conformations, vibrational absorption (VA, harmonic and anharmonic) and vibrational circular dichroism (VCD) spectra for conformers of monomeric chiral d(-)-lactic acid and their complexes with water at the DFT(B3LYP)/aug-cc-pVDZ and DFT(B3LYP)/aug-cc-pVTZ levels. A detailed analysis has been performed principally for the two most stable complexes with water, differing by lactic acid conformation. The VCD spectra were found to be sensitive to confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 33 publications
9
52
0
Order By: Relevance
“…4) had lengths of 1.73–2.13 Å, which is very consistent with results previously observed for L ‐alanine (1.75–1.95 Å) 11. Previous optimization studies of the structures of LA and D ‐lactic acid with a few water molecules in vacuo and PCM suggested that both compounds take the most stable conformation when intramolecular hydrogen bonds are formed between the OH and COO − groups 22, 23, 33. However, no such intramolecular hydrogen bond was formed in any of the optimized structures with seven water molecules, and the COO – and OH groups formed hydrogen bonds with the water molecules only.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…4) had lengths of 1.73–2.13 Å, which is very consistent with results previously observed for L ‐alanine (1.75–1.95 Å) 11. Previous optimization studies of the structures of LA and D ‐lactic acid with a few water molecules in vacuo and PCM suggested that both compounds take the most stable conformation when intramolecular hydrogen bonds are formed between the OH and COO − groups 22, 23, 33. However, no such intramolecular hydrogen bond was formed in any of the optimized structures with seven water molecules, and the COO – and OH groups formed hydrogen bonds with the water molecules only.…”
Section: Resultssupporting
confidence: 89%
“…The hydrated structure of L ‐alanine could be optimized with six water molecules around the COO − group and three water molecules around the NH 3 + group 11. On the other hand, Sadlej et al successfully optimized the hydrated structure of D ‐lactic acid with one water molecule around the OH group using the DFT method 22. Therefore, we constructed eight initial structures of LA with one and six water molecules around the OH and COO − groups, respectively, for dihedral‐angle pairs (ϕ, φ) of (0°, −90°), (0°, 0°), (0°, 90°), (0°, 180°), (90°, −90°), (90°, 0°), (90°, 90°), and (90°, 180°).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] Recently, it has been shown that the VCD method can also be a powerful tool in studying the intermolecular interactions of chiral molecules. [46,47] Continuing our previous study, [35] we undertook a detailed investigation on the conformation behavior of gas-phase cysteine isolated in low-temperature Ar and N 2 matrices. The experimental findings are interpreted by means of the anhar- Conformer no.…”
Section: (Sh)cha C H T U N G T R E N N U N G (Nhmentioning
confidence: 99%
“…The quantum chemical method used was HF or B3LYP, 41 and the basis sets used were 6311 þ G*, [42][43][44] TZVP [45][46][47] and cc-pVTZ. [48][49][50][51][52] The conformational energy calculation was also performed for isotactic and syndiotactic dimer model compounds for the preferred conformations selected from the Ramachandran map of the monomer model compound.…”
Section: Conformational Energy Calculationmentioning
confidence: 99%